3D Reconstruction Based on Fusing Active Structured Laser and Passive Stereo Techniques - Al-Saqal, Shahad A.; Al-Temeemy, Ali A. (Al-Nahrain Journal for Engineering Sciences, 2020)
Three-dimensional reconstruction of real objects comprises capturing the appearance and the shape for these objects and determining the three-dimensional coordinates for their profiles. This reconstruction process can be accomplished either by using active or passive techniques. In this paper, a new fusion method is proposed for 3D reconstruction. This method exploits the advantages of both stereo-based passive and laser-based active techniques and overcomes their limitations to improve the performance of 3D reconstruction. With this method, a hybrid laser-based structured light scanning system is designed and implemented. This system captures the required information using passive and active techniques and uses the proposed fusion method for 3D reconstruction. The performance of the proposed method and its scanning system were experimentally evaluated. The evaluation results show high reconstruction performance for the proposed fusion method over the traditional 3D reconstruction techniques. The results also show the effectiveness of the hybrid laser scanning system and its ability to scan and reconstruct the shape and the appearance for real objects using the proposed fusion method.